Recombinant truncated E protein as a new vaccine candidate against nontypeable H. influenzae: Its expression and immunogenic evaluation. (September 2017) - Behrouzi, Ava; Bouzari, Saeid; Vaziri, Farzam; Fateh, Abolfazl; Afrough, Parviz; Vijeh Motlagh, Atefeh Davoudi; Siadat, Seyed Davar
Abstract: Protein E (PE) is a conserved entity observed in both nontypeable Haemophilus influenzae (NTHi) and encapsulated H. influenzae . This is a small surface lipoprotein, consisting of only 160 amino acids, involved in the adhesion of H. influenzae to various types of epithelial cells. A 384-bp-long fragment from NTHi PE was cloned into the prokaryotic expression vector pBAD-gIIIA. The recombinant protein was expressed with arabinose and then purified by affinity purification on an Ni - NTA agarose matrix. BALB/c mice were immunized by subcutaneous injection with purified recombinant truncated PE mixed with an alum adjuvant. Serum antibody response and the functional activity of antibodies were evaluated by enzyme-linked immunosorbent assay (ELISA) and serum bactericidal assay (SBA), respectively. Colony PCR, double digestion, and sequencing were used to verify successful cloning of truncated PE. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and western blot analyses indicated the presence of a ∼15-kDa recombinant protein. Serum IgG, IgG1, and IgG2a levels were significantly higher in the group immunized by recombinant truncated PE mixed with an alum adjuvant, compared to the non - vaccinated control group. Development of a strong bactericidal effect against NTHi was observed in the serum samples from immunized animals. Our findings suggest that recombinant truncated PE is a potential vaccine candidate for NTHi. Highlights: The aim of this study was to assess the efficiency and potential of truncated E protein nontypeable Haemophilus influenzae as a vaccine candidate in animal models. The evaluate its protective efficacy based on Serum bactericidal activity responses.